2014
DOI: 10.7575/aiac.ijels.v.2n.1p.58
|View full text |Cite
|
Sign up to set email alerts
|

Grammar Translation Method (GTM) Versus Communicative Language Teaching (CLT); A Review of Literature

Abstract: Methodology is one of the important elements to implement he objective of education in teaching learning process particularly in English classes. To give the information about two phenomenal methods namely GTM and CLT is the main purpose of this scientific writing since GTM is commonly used previously and CLT is very famous nowadays. In so doing, the strength of this paper is to improve the knowledge of educational practitioners especially in method of teaching English. The comparison between the two methods i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 4 publications
3
12
0
5
Order By: Relevance
“…The communicative approach establishes a direct bond between the experience and the expression [16]. It is very beneficial for the learners; once they finished their training, they have to join the professional life; they need a real context to become a useful part of society [28,29]. Studies conducted by [29] and [21] also supported the findings of this study.…”
Section: Discussionsupporting
confidence: 77%
“…The communicative approach establishes a direct bond between the experience and the expression [16]. It is very beneficial for the learners; once they finished their training, they have to join the professional life; they need a real context to become a useful part of society [28,29]. Studies conducted by [29] and [21] also supported the findings of this study.…”
Section: Discussionsupporting
confidence: 77%
“…Based on these key concepts of CLT, previous studies have demonstrated the benefits of implementing CLT in regard to boosting ELLs' communicative competence, vocabulary development, and productive skills, including listening and speaking (Natsir & Sanjaya, 2014;Safraz, Mansoor, & Tariq, 2015;Tuba, 2013). For instance, Tuba (2013) examined ELLs' vocabulary development and retention by comparing the GTM and CLT through controlled and experimental groups.…”
Section: Communicative Language Teachingmentioning
confidence: 99%
“…The study results indicated that the overall perceptions of the teachers and students show a positive attitude towards the communicative language teaching approach. Some research in ELT has argued that CLT is an effective teaching method that can be used to enhance ELLs' second and foreign language learning because it fosters ELLs' communicative competence through authentic input and practice (Natsir & Sanjaya, 2014;Safraz, Mansoor, & Tariq, 2015;Tuba, 2013).…”
Section: Communicative Language Teachingmentioning
confidence: 99%
“…Learning L2 reading is taken as a global communication process (Natsir & Sanjaya, 2014). This implies connecting linguistic and communicative skills in a global and circular model of learning where there is a continuous feedback among all language skills as in CLT and CLIL.…”
Section: Introductionmentioning
confidence: 99%